2017
DOI: 10.1016/j.ultramic.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Medipix3 detector for 60 and 80 keV electrons

Abstract: In this paper we report quantitative measurements of the imaging performance for the current generation of hybrid pixel detector, Medipix3, used as a direct electron detector. We have measured the modulation transfer function and detective quantum efficiency at beam energies of 60 and 80keV. In single pixel mode, energy threshold values can be chosen to maximize either the modulation transfer function or the detective quantum efficiency, obtaining values near to, or exceeding those for a theoretical detector w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 18 publications
1
66
0
Order By: Relevance
“…Experimental images were obtained in Fresnel mode using a JEOL ARMcF operated at 200kV [33]. Additionally, we used a pixelated detector, Medipix3, to acquire images rather than a traditional CCD camera due to superior noise performance [34]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental images were obtained in Fresnel mode using a JEOL ARMcF operated at 200kV [33]. Additionally, we used a pixelated detector, Medipix3, to acquire images rather than a traditional CCD camera due to superior noise performance [34]. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MAPS detectors are more suited to higher electron energies due to their reduced thickness, which minimizes electron scattering within the sensor (McMullan et al, 2014(McMullan et al, , 2009. The Medipix family of hybrid pixel detectors (Llopart et al, 2002;Ballabriga et al, 2011) have previously shown good spatial resolution between 60-120 keV electron energies (McMullan et al, 2007(McMullan et al, , 2009Mir et al, 2017). However, hybrid pixel detectors are currently not suited to high-resolution imaging of electrons with energies above 100 keV due to their large point spread, but, unlike monolithic detectors, hybrid pixel detectors are ideally suited for measuring electron diffraction patterns due to their high dynamic range, on-pixel electroncounting capabilities, radiation hardness and high frame rate (Nederlof et al, 2013;van Genderen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CSM was originally conceived to handle multi-pixel events arising from spreading of the secondary electron-hole charge under diffusion. For high energy electrons, we have shown that the algorithm can provide simultaneous improvement of both the DQE and MTF for energies in the range 60-80 keV [20], therefore correcting for lateral spreading in the sensor of the primary radiation also. The process of detecting and counting an incident primary electron is now discussed for two cases with close reference to Figure 1 Following the electron arrival, e-h pair charge generated in the sensor volume along the path traveled by the primary electron moves under the applied bias and this movement induces a signal at the readout pixel electrodes.…”
Section: Medipix3 Hybrid Pixel Architecture and Temporal Imagingmentioning
confidence: 99%
“…When operating in CSM, it is sensible to set the THA threshold to a low value (so that all individual pixels in an event cluster are considered) and THB to a higher value. Since the latter operates on summed charge, the DQE performance is improved, provided primary electron energies have an average lateral spread that is less than the 2 × 2 pixel block size [20]. The count dependence on threshold value for CSM and SPM are shown in Figure 5(a).…”
Section: Optimising Time Resolutionmentioning
confidence: 99%